2015
DOI: 10.1002/qua.24957
|View full text |Cite
|
Sign up to set email alerts
|

Improving approximate determination of the noninteracting electronic kinetic energy density from electron density

Abstract: This work describes a new approach for approximate obtaining the positively defined electronic kinetic energy density (KED) from electron density. KED is presented as a sum of the Weizs€ acker KED, which is calculated in terms of electron density exactly, and unknown Pauli KED. The latter is presented via local Pauli potential and Gritsenko-van Leeuwen-Baerends kinetic response potential, to which the second-order gradient expansion is applied. The resulting expression for KED contains only one empirical param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 120 publications
(131 reference statements)
0
42
0
Order By: Relevance
“…A detailed discussion of application of the experimental ED in the DFT formalism can be found in Refs. [77,78,79]. We used the experimental electron density and its derivatives expressed in terms of Hansen-Coppens space-extended multipole structural model [80]; in computations, the actual values of these quantities at each point r have been employed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed discussion of application of the experimental ED in the DFT formalism can be found in Refs. [77,78,79]. We used the experimental electron density and its derivatives expressed in terms of Hansen-Coppens space-extended multipole structural model [80]; in computations, the actual values of these quantities at each point r have been employed.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, distribution of the isotropic internal pressure of the inhomogeneous electron fluid caused by quantum kinetic and exchange effects equals to ( ) ( [76] or by using some other similar DFT approximations, see [77]. Usually approximate functions ( ) s t r show a wrong asymptotic behavior close to the nuclei positions.…”
Section: Methodsmentioning
confidence: 99%
“…Some quantities are frequently used on BCP to capture the bond specific features and among them, kinetic energy density (KED) at the BCP can be the form of Gc=2.8173×ρc5/3+2ρc/6 in the gradient expansion approximation . Seriani showed that the KED at the BCP is associated with the band gap for alkali and alkaline‐earth oxides . Seriani reported that the band gap of oxides of alkali and alkaline‐earth metals linearly depends on the KED at the BCP.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16] There are some new developments in applying and understanding the Ghosh-Berkowitz-Parr entropy. [17][18][19][20][21][22][23] The local temperature of Ghosh et al was defined via the kinetic energy density and varies from point to point. However, the kinetic energy density is not uniquely defined.…”
mentioning
confidence: 99%